Competitive Altruism and Endogenous Reference Group Selection in Private Provision of Environmental Public Goods - Heinz Welsch; Jan Kühling (University of Oldenburg, Department of Economics, 2012)
We develop and test a model of social comparison in which individuals gain status through pro-social behavior (competitive altruism) and in which they endogenously choose the reference group and associated reference standard involved in signaling status (reference group selection). In our framework of private provision of environmental public goods, the optimal reference standard involves a balance between the magnitude of the status signal (implying a low reference standard) and the higher value of the signal in a greener social environment. By using a unique set of survey data we find evidence of (a) respondents behaving in a competitively altruistic fashion and (b) reference persons' intensity of pro-environmental behavior depending on relevant attitudes of the respondents, consistent with predictions from our framework of reference group selection.
Keywords: D64; H31; H41; Q00; 330; competitive altruism; reference groups; endogenous reference standard; pro-environmental behavior; private public good provision; Umweltschutz; Öffentliche Güter; Privatwirtschaft; Altruismus; Nachfrageinterdependenz; Theorie; Deutschland